Effects of staff education and standardizing dosing and collection times on vancomycin trough appropriateness in ward patients - Hammond DA; Atkinson LN; James TB; Painter JT; Lusardi K (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Many institutions have guidelines for initiation and monitoring, but not timing, of vancomycin. Objective: Our objective was to evaluate vancomycin trough collection appropriateness before and after an initiative to change the dosing and trough collection times in ward patients. Methods: A retrospective cohort study of ward patients from May 2014-16 who received scheduled intravenous vancomycin was performed. Nurse managers and pharmacists provided staff education. Differences between pre- and post-intervention groups were compared using student's t-test for continuous data and chi-square test for categorical data. Results: Baseline characteristics were similar between the pre-intervention (n=124) and post-intervention (n=122) groups except for weight-based maintenance dose (15.3 mg/kg vs. 16.5 mg/kg, p=0.03) and percentage of troughs collected with morning labs (14% vs. 87%, p<0.001). Patients in the pre- and post-intervention groups received a similar frequency of loading doses (14.5% vs. 16%, p=0.68). There was no significant difference in percentage of vancomycin troughs collected appropriately at 30 (40% vs. 42%, p=0.72), 60 (57% vs. 63%, p=0.35), or 75 (60% vs. 68%, p=0.22) minutes from the scheduled time of the next dose. Conclusion: Staff education and standardizing collection of vancomycin troughs with morning blood collections did not affect the percentage of appropriately collected vancomycin troughs.